Technological and Industrial Applications Associated With Industry 4.0 - Ochoa-Zezzatti, Alberto; Oliva, Diego; Hassanien, Aboul Ella.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book includes chapters related to the analysis of cultural differences as a tool to enrich tacit knowledge and make processes more efficient, the factors that influence job satisfaction and the value of social capital as a competitive strategy to achieve productivity and competitiveness of organizations, in addition to research of the utmost importance to discover the facets of the diamond with respect to the symbolic capital of the organizations where Generation Z will work and how it will discover the best time to establish an innovation ecosystem that will influence its work trajectory. Industry 4.0 requires a major paradigm shift, since human capital is a source of competitive advantage. Being competitive enables to a company, a region, a society or a country the power to advance in different areas, contributing to the benefit of a social group, therefore, and organizations need to make efforts that lead to adding value and generate a competitive advantage. Industrial applications based on artificial intelligence can change our lives in just one generation. The chapters in this book show progress and challenges related to real-world applications, as well as the need to strengthen human capital to achieve systemic and comprehensive competitiveness required in the XXI century. .
Implementation of an intelligent model based on Convolutional Neural Network for the detection of diseases in citrus crops caused by bird pests using an intelligent drone -- Intelligent application to detection of arachnid bites in children implementing deep learning techniques, an AmI-based solution -- Financial analysis over the smartest companies. .
Keywords: Industrial engineering; Production engineering; Computational intelligence; Industrial and Production Engineering; Computational Intelligence; Industry 4.0